Design of Motorcycle-Passenger Ship (Klotok) Catamaran Type for Kampung Baru Balikpapan - Penajam Paser Utara - Suardi Suardi; Rizky Risaldo; Andi Mursid Nugraha Arifuddin; Amalia Ika Wulandari; Wira Setiawan; Muhammad Uswah Pawara; Alamsyah Alamsyah (Institut Teknologi Sepuluh Nopember, 2023)
Balikpapan City has an area of 508.9 km2 which has 646,727 people living here. Balikpapan City is also known as a port city because it has two domestic ports namely Kampung Baru Port and Semayang Port. Currently, the port of Kampung Baru is still active in carrying out daily activities, namely the klotok boat crossing and also the dock for motor boats berths. The condition of mobility for crossing vessels in the port of Kampung Baru that uses boat klotok is inadequate due to the lack of supporting components for access to the ship so the safety of this port is questioned. besides that, klotok ships are also only able to carry a maximum of 21 passengers and 5 motorcycles and access to loading and unloading exits is very unsafe. The purpose of this study is to design a crossing ship that can be used safely for transportation for passengers and motorcycles that will pass the sea lane for crossing to the North Penajam Paser area. The ship is designed to have an easy access door or ramp door for passenger and motorcycle mobility to improve the safety of crossings at the port of Kampung Baru. The parent Design Approach method is used in this project, this method is one way of designing a ship using comparison or comparison, namely by taking a ship that is used as a reference for a comparison ship that has the same characteristics as designed ship. The main focus to be achieved in this research obtained a General Arrangement which has more cargo than the klotok ship with a capacity of 25 passengers and 10 motorcycles, and the dimension of the ramp door used in this final project is L 1.50 m and B 1.50 m. The Principal dimension of the ship obtained in this research is Loa = 12.50 m, Lpp = 11.50 m, Lwl = 11.96 m, B = 5.75 m, B1 = 1.64 m, H = 1.8 m, T = 0.85 m, Cb = 0.56, Vs = 15 Knots. The results of this study provide a good idea of the modernization of a comfortable ferry fleet for this area.